Assessment of animal diversity in degraded forest areas (Zoological Records and Reviews, 2023)
Forest degradation -- the partial loss of forest structure, composition, and ecological function without completeconversion -- affects far greater areas of tropical forest than outright deforestation, yet its consequences for animalbiodiversity are less thoroughly documented. Degraded forests retain some structural complexity and species, butselective logging, fuelwood extraction, grazing, and repeated fire alter canopy cover, understorey structure, and speciescomposition in ways that differentially affect animal communities across taxonomic groups and functional guilds. Thisstudy presents a comprehensive assessment of animal diversity across a forest degradation gradient in the EasternGhats of Andhra Pradesh, comparing intact forest, lightly degraded forest, moderately degraded forest, and heavilydegraded scrub at 48 sites surveyed using standardised camera trapping, bird point counts, herpetofauna VES, andinvertebrate sampling over two years (2021-2023). A total of 384 animal species from five groups are documented. Allgroups showed significant species richness declines with degradation intensity, but at different rates: large mammalsdeclined most steeply (-72.4% from intact to heavily degraded), while generalist birds showed the smallest decline(-18.4%). Canopy cover, understorey structural complexity, and distance from nearest intact forest are the threestrongest predictors of animal diversity. Recovery trajectories under active restoration are assessed. Managementrecommendations for biodiversity-sensitive forest management and restoration are presented.
Keywords: degradation gradient; birds; mammals; Andhra Pradesh; restoration ecology; selective logging; camera trapping; Eastern Ghats; animal diversity; forest degradation